Risk Analysis of the Influence of Work Methods, Equipment and K3, and Land Affected by the Community on the Implementation of the Coastal Safety Development Project on the Coastal Jakarta Bay Phase 6 Package 4 - Widhitomo, Kurniawan; Azhar, Moh.; Raharjo, Sri Kustoyo (SEAN Institute, 2024)
DKI Jakarta Province and its surroundings often experience flood events. The causes of flooding include increased rainfall intensity, large-scale land conversion and insufficient river capacity to accommodate flood discharge. In addition, land subsiversion in several locations of Jakarta Beach caused a storm that inundated residential areas and other strategic areas. Related to that, the construction of embankments and the construction of coastal safety needs to be carried out. In the implementation of the work there are problems such as the working method of Equipment, K3, Social community and land, the four problems do affect the time of project implementation, the scope of this research is carried out in the project package 4 coastal safety of the capital and the project is still running. The purpose of this study is to determine the influence of occupational safety risks, equipment, and the social influence of the community around the project on the implementation time. Meanwhile, data is taken either secondary (work reports or other literature, both secondary and primary).